2019
DOI: 10.1021/acsami.9b13353
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Engineered Silicon-Based Sandwich Nanomat as Flexible Anode for Lithium-Ion Batteries

Abstract: Lithium-ion batteries with high electrochemical performance and stable mechanical compliance are pivotal to propel the advanced wearable electronics forward. Herein, a high-conductive flexible electrode densified from multilayer lamellar unit cells with the silicon-based sandwich structure is rationally designed by molecular engineering. Silicon nanoparticles can be uniformly anchored to the surface of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized bacterial cellulose (TOBC) aerogel through hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 56 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…5 However, a Si-based anode generally suffers from a series of problems. The main challenges for practical applications include the following: (i) huge volume change of Si in repeated charge−discharge cycles, causing pulverization as well as continuous formation of unstable solidelectrolyte interphase (SEI); 6 (ii) irreversible capacity loss at the first cycle, leading to low initial coulombic efficiency (ICE); 7 and (iii) small packing density of active materials, resulting in low volumetric capacity. 8 To suppress volume change during charge−discharge cycles, nano-engineered Si materials have been intensively studied and successfully applied to prevent pulverization, as their large surface-to-volume ratio can facilitate stress relaxation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, a Si-based anode generally suffers from a series of problems. The main challenges for practical applications include the following: (i) huge volume change of Si in repeated charge−discharge cycles, causing pulverization as well as continuous formation of unstable solidelectrolyte interphase (SEI); 6 (ii) irreversible capacity loss at the first cycle, leading to low initial coulombic efficiency (ICE); 7 and (iii) small packing density of active materials, resulting in low volumetric capacity. 8 To suppress volume change during charge−discharge cycles, nano-engineered Si materials have been intensively studied and successfully applied to prevent pulverization, as their large surface-to-volume ratio can facilitate stress relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…However, a Si-based anode generally suffers from a series of problems. The main challenges for practical applications include the following: (i) huge volume change of Si in repeated charge–discharge cycles, causing pulverization as well as continuous formation of unstable solid-electrolyte interphase (SEI); (ii) irreversible capacity loss at the first cycle, leading to low initial coulombic efficiency (ICE); and (iii) small packing density of active materials, resulting in low volumetric capacity …”
Section: Introductionmentioning
confidence: 99%
“…The microscroll nanoarchitecture holds new insights in developing large‐scale and actual capacity of the commercial cellulose‐based carbon/silicon electrodes for LIBs. In addition, to fabricate the Si‐based anode with durable cyclability and mechanical property, Si nanoparticles and graphite microsheets were assembled on 2,2,6,6‐tetramethylpiperidine‐1‐oxyl (TEMPO) oxidized bacterial cellulose aerogel through hydrogen bonding to form a free‐standing anode for LIBs, which showed an exceptional deformation tolerance, reliable stability, and improved rate capability [37] …”
Section: Natural Cellulose Substances Based Self‐supporting Binder‐frmentioning
confidence: 99%
“…[136] Therefore, developing as train-free Si-based anode with good flexibility and satisfactory electrochemical performances has been identified as an attractive and challenging task for satisfying the needs of flexible LIBs that are durable under rolling and bending. Zhou et al [131] reported the preparation of aS i-based self-standingf ilm with ac ompact sandwich-like structure in the presence of BC and graphitem icrosheets (GM) and explored its application in flexible all-in-oneL IBs (Figure 17 a). The strongi nterconnections from hydrogen bonding between OH/COOHg roups of BC nanofibers and silanol functionalities ensure uniform distributiono ft he generatedS i nanoparticles.…”
Section: Lithium-ionb Atteriesmentioning
confidence: 99%